2018
DOI: 10.2298/sos1804477d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sintering temperature on Cu-CNTs nano composites properties produced by PM method

Abstract: In this research work, copper and CNTs have been processed using high energy milling in different milling times (5, 10 and 15 hours). FESEM and XRD have been used to characterize the milled powders. The FESEM micrographs of the milled powders indicated that the morphology of powders changed from spherical shape to flake as milling time increased. The effect of sintering temperature as well as CNTs content on the properties of Cu-CNTs nanocomposite has been investigated. The optimum sintering temperature to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…By increasing the sintering temperature, both experimental and relative densities were significantly increased. At higher sintering temperatures, a denser structure was formed due to higher diffusion rates [30][31][32]. [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…By increasing the sintering temperature, both experimental and relative densities were significantly increased. At higher sintering temperatures, a denser structure was formed due to higher diffusion rates [30][31][32]. [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a good dispersion of CNTs is challenging to reach because of its high aspect ratio [24]. To overcome this disadvantage, more excellent dispersion and adherence methods require mechanical milling, ultrasound, magnetic stirring, and the modification of the surface energy of CNTs [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have concluded that MA is a valuable technique for the homogeneous dispersion of CNTs in the metal matrix [24,25,30]. However, MA provokes possible damage to CNTs, and mixing at the molecular level leads to an interface [24].…”
Section: Introductionmentioning
confidence: 99%
“…P/M compacts are produced by mixing pure or alloy powders, being compressed within a mould and being heated in order to allow the metal powders to form a metallurgical bond [3]. Sintering [4,5] is the method of producing components, of which density can be kept under control, and of which resistance & integrity are formed through the implementation of thermal energy to the metal powders in a temperature under the fusion temperature. When thermal energy is applied on compressed metal powder, the component condensates, and the average particle size level increases; this condensation and the increase in the particle size is named as sintering [6].…”
Section: Introductionmentioning
confidence: 99%